Analysis of Stock Portfolio Performance Using Passive Strategy and Active Strategy with Single Index Model - Ricki, Ricki; H. Mustafa, Matrodji (Keynesia : International Journal of Economy and Business, 2023)
This study aims to determine and analyze the differences in return and risk performance results of passive and active strategies using the Single Index Model. Then measure the return performance using the Sharpe Index, Treynor, and Jensen's Alpha. This research was conducted on Sri-Kehati index stocks for the period November 2019 to November 2021. Based on passive portfolio strategy research, there are three stocks that form the optimal portfolio, namely BBCA, BBRI, SIDO. While based on active portfolio strategy research, in the first year there were three stocks that formed the optimal portfolio, then in the second year there were seven stocks forming the optimal portfolio, namely BBCA, BBRI, DSNG, INCO, SIDO, SMGR, WIKA. Based on performance measurement using Sharpe, Treynor and Jensen's Alpha indices, the Active Portfolio Strategy is better than the Passive Portfolio Strategy. Meanwhile, based on the difference test using the Mann Whitney U test method, it can be concluded that there is no significant difference in return performance between passive and active portfolio strategies.